Dampak Korupsi Pertamax Oplosan Terhadap Kepercayan Publik - Siti Isyfaiyah; Tika Dwi Istiani; Irfa Rosyi Safira; Elsa Indah Sanjaya (Jurnal Sosial-Politika, 2025)
The Pertamax bootlegging corruption case, which took place from 2018-2023 and was revealed in early 2025, has cost the state around IDR 193.7 trillion. The modus operandi involved the purchase of Pertalite (RON 90) at the price of Pertamax (RON 92) by PT Pertamina Patra Niaga, which was then bootlegged with lower octane fuel at private depots, then sold as Pertamax. Consumers paid a high price for inappropriate quality. Seven defendants, including high-ranking Pertamina officials and private parties, have been indicted. The impact of this case spans multiple sectors: economic (state losses, market distortions, potential decline in investment), social (injustice, public unrest, consumer losses in the form of vehicle damage), and political/governance (weakened institutions, reform challenges, negative perceptions of government capability). The survey showed 86.4% of the customers felt aggrieved and 55.3% experienced vehicle damage. The case also reduced public trust in the government and Pertamina, showed weaknesses in oversight in national energy governance and threatened Pertamina's business.